The new post-oil Arab Gulf managing people and wealth - Sultan, Nabil A.; Weir, David; Karāk Šalhūb, Zainab 1955- (Saqi, 2011)
Sultan, Nabil A.: Introduction. - S. 9-14 Sultan, Nabil A.; Metcalfe, Beverly Dawn; Weir, David T. H.: Building the foundation for a post-oil era : the case of the GCC countries. - S. 15-43 Karake-Shalhoub, Zeinab: GCC sovereign wealth funds and Islamic finance : financial foundations for the post-oil Gulf? - S. 45-72 Weir, David T. H.; Sultan, Nabil A.; Metcalfe, Beverly Dawn; Abuznaid, Samir Ahmad: The GCC countries as knowledge-based economies : future aspirations and challenges. - S. 73-96 Davidson, Christopher M.: Higher education in the Gulf states : from traditional to modern. - S. 97-116 Senteni, Alain; Tamim, Rana; Holmes, Bryn; Gledhill, Paul Michael: A 'smart' technology-enhanced learning for the post-oil Arab Gulf. - S. 117-142 Metcalfe, Beverly Dawn; Sultan, Nabil A.; Weir, David T. H.: The role of women in a post-oil Arab Gulf future. - S. 143-174
Enthält 6 Beiträge
Keywords: Economic forecasting--Persian Gulf States--Congresses.; Persian Gulf States--Economic conditions--21st century--Congresses.; Persian Gulf States--Forecasting--Congresses.; Persian Gulf States--Politics and government--21st century--Congresses.; Persian Gulf States--Social conditions--21st century--Congresses.; Gulf Cooperation Council / (DE-588)2088427-8 / (DE-627)100329853 / (DE-576)192599038; Strukturwandel / (DE-627)091393264 / (DE-2867)11790-4; Erdölvorkommen / (DE-627)091357756 / (DE-2867)19387-4; Staatsfonds / (DE-627)547185596 / (DE-2867)29702-2; Islamisches Finanzsystem / (DE-627)091369177 / (DE-2867)18177-6; Wissensmanagement / (DE-627)091401496 / (DE-2867)19655-5; Bildungsinvestition / (DE-627)091352010 / (DE-2867)11222-6; Frauen / (DE-627)091361087 / (DE-2867)15920-4; Mittlerer Osten / (DE-627)091378419 / (DE-2867)17608-3